An Investigation of Extended Proinov Contraction under Non-Triangular Metric Structure and the Corresponding Applications - Ram Jeevan; Jayesh Savaliya; Dhananjay Gopal (Science & Technology Asia, 2025)
This article demonstrates several fixed point theorems of extended Proinov-type, on the existence and uniqueness of fixed points within the context of non-triangular metric spaces. Additionally, we provide two applications of our primary result, in solving existence and uniqueness of a solution for a non-homogeneous linear parabolic partial differential equation and a stochastic integral equation.